Flavonoid Glycoside Constituents from the Leaves of Hibiscus Tiliaceus - Le, Huyen Tram; Tran, Thu Huong; Nguyen, Van Thong; Nguyen, Hoang Minh (JST: Engineering And Technology For Sustainable Development, 2021)
Hibiscus tiliaceus L. is a typical plant of tropical climate and found in the regions of mangroves in Vietnam. It is also one of the most common secondary trees and is frequently seen in mangrove forests. In spite of all part of this plant are used in folk medicine, studies of its chemical constituent have been very little. Four flavonoids (1‒4) were isolated from a methanolic extract of H. tiliaceus leaves (Malvaceae) using various chromatographic separations. Their structures were elucidated to be astragalin (1), isoquercitrin (2), rutin (3), and trans-tiliroside (4) by detailed analysis via spectroscopic techniques (1D, 2D NMR, and ESI-MS data) as well as comparison with those reported.